Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Loyalitas Karyawan Pada DPD Provinsi Jawa Barat - intan, Intan Merlina Rahayu; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Amid the complexities of political organizations, employee loyalty emerges as a crucial element in maintaining operational stability and sustainability. This study stems from the awareness that internal factors such as leadership style and work environment play a significant role in shaping long-term employee commitment to the organization. Conducted at the Regional Leadership Council (DPD) of the Gerindra Party in West Java Province, this research adopts a quantitative approach by distributing questionnaires to internal staff. The findings reveal that a communicative, participative, and consistent leadership style has a significant positive influence on employee loyalty. Likewise, a supportive, harmonious, and conducive work environment strengthens employees’ emotional and professional attachment to the organization. These results affirm that in the context of political institutions, cultivating healthy workplace relationships and visionary leadership not only improves performance but also reinforces loyalty as a foundation for organizational sustainability